Modularly engineered alginate bioconjugate hydrogel as biocompatible injectable scaffold for in situ biomineralization. (1st April 2020) - Kim, Seong Han; Thambi, Thavasyappan; Giang Phan, V.H.; Lee, Doo Sung
Highlights: Injectable bioconjugates were synthesized by the post modification of alginate. Bioconjugates exhibited sol-gel transition between room and body temperature. Bioconjugate gels in SBF showed the nucleation and growth of hydroxyapatite. BMP 2-loaded bioconjugate hydrogel exhibited in situ biomineralization in vivo . Abstract: In the present study, a type of bioconjugate was synthesized by post modification of alginate by conjugating temperature-responsive poly(ε-caprolactone- co -lactide)- b -poly(ethylene glycol)- b -poly(ε-caprolactone- co -lactide) and O -phosphorylethanolamine as phosphorylation functional groups. Freely flowing bioconjugate sols at low temperature can transform to stable viscoelastic gels at the physiological temperature (37 °C). Subcutaneous administration of temperature-responsive bioconjugate sols into the dorsal region of Sprague-Dawley rats formed in situ hydrogel. in situ formation of bioconjugate gels in stimulated body fluids at 37 °C showed nucleation and hydroxyapatite mineral growth. Furthermore, hydroxyapatite growth was also found in in vivo gels, which suggested the potential of alginate-based bioconjugate gels as a scaffold for bone engineering. Bone morphogenetic protein 2 (BMP-2)-loaded bioconjugate formed stable gel in vivo, and demonstrated sustained release. BMP-2-loaded bioconjugates exhibited in situ biomineralization in vivo . These results imply that the in situ formation of injectable biomimetic materials has potential for bone tissue engineering applications.